Experimental and numerical analysis of the thermal performance of pebble solar thermal collector - Naik, N. Channa Keshava; Priya, R. Krishna; Agulut, Umit; Gurel, Ali Etem; Shaik, Saboor; Alzaed, Ali Nasser; Alwetaishi, Mamdooh; Alahmadi, Ahmad Aziz (CELL PRESS, 2024)
In this work, pebbles of higher specific heat than the conventional absorber materials like aluminium or copper are proposed as a absorber in the solar flat plate collector. The proposed collector are integrated into the building design and constructed with masonry. Tests were conducted by varying the operating parameters which influence its performance, like the flow rate of the heat-absorbing medium, and the tilt of the collector using both coated and uncoated pebbles. The maximum temperature difference that could be measured for a conventional absorber was approximately 8 degrees C for a flow rate of 0.6 L/min. While for a coated and uncoated absorber, it was 7 degrees C and 5.5 degrees C respectively. This difference decreased with an increase in flow rates from 0.6 L/min to 1.2 L/min. For all the flow rates, it was observed that the average difference in efficiency between the coated and the conventional absorber collector is 5.82 %, while the difference between the coated and uncoated absorber collector is 15.68 %. Thus, it is very much evident that by replacing the conventional absorber with the proposed coated pebble absorber, the overall loss in efficiency is just 5.82 %, but the advantages are enormous. Along with the experimental study, numerical analysis was also carried out with CFD modeling. The numerical results agreed well with experimental results with the least error. Therefore, CFD simulation can be further used to optimize the design of the collector.
Keywords: Pebbles; Flat plate collector; Heat gain enhancement; Thermal efficiency; CFD; ABSORBER PLATE; AIR HEATER; WATER; ENERGY; STILL; STORAGE; SYSTEM; ROUNDNESS; EXERGY; DESIGN; Science & Technology - Other Topics